2010
DOI: 10.1128/jb.00358-10
|View full text |Cite
|
Sign up to set email alerts
|

RpoS, the Stress Response Sigma Factor, Plays a Dual Role in the Regulation of Escherichia coli 's Error-Prone DNA Polymerase IV

Abstract: RpoS, Escherichia coli's general stress response sigma factor, regulates error-prone DNA polymerase IV (Pol IV) (encoded by the dinB gene). Pol IV is induced in stationary-phase cells, and thereafter, levels of the protein remain elevated for several days of continuous incubation. This induction and persistence in stationary-phase cells are dependent on RpoS. Data presented here show that this regulation is direct via the RpoS-directed transcription of the dinB gene. However, a loss of RpoS also results in a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
40
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 41 publications
0
40
0
Order By: Relevance
“…For example, the presence of a copy of the dinB gene on the FЈ episome in addition to the copy on the chromosome results in 4-fold more Pol IV and a 2-to 3-fold increase in mutation frequencies (22,36). The presence of the dinB gene on a multicopy plasmid results in 10-to 20-fold more Pol IV (36,73) and, depending on the mutational target, 5-to 200-fold increases in mutation frequencies (37,39,63,65,70,73,75). These observations strongly suggest that the mutagenic activity of Pol IV normally is tightly regulated in growing cells but that even a modest increase in abundance allows Pol IV to, at least partially, escape this regulation.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…For example, the presence of a copy of the dinB gene on the FЈ episome in addition to the copy on the chromosome results in 4-fold more Pol IV and a 2-to 3-fold increase in mutation frequencies (22,36). The presence of the dinB gene on a multicopy plasmid results in 10-to 20-fold more Pol IV (36,73) and, depending on the mutational target, 5-to 200-fold increases in mutation frequencies (37,39,63,65,70,73,75). These observations strongly suggest that the mutagenic activity of Pol IV normally is tightly regulated in growing cells but that even a modest increase in abundance allows Pol IV to, at least partially, escape this regulation.…”
mentioning
confidence: 57%
“…In addition, RpoS has been found by transcription microarray analysis to regulate directly or indirectly almost 300 genes in exponential-phase cells (14a). Recently, we found that RpoS drives the transcription of dinB in stationary-phase cells but not in exponential-phase cells; and yet, RpoS still affects Pol IV activity in exponential phase (63). In exponentially growing cells, overexpression of Pol IV from an RpoS-independent promoter increases the growth-dependent mutation rate 10-fold, but in cells lacking RpoS, this increase is only 4-fold, even though the amount of Pol IV is unchanged (63).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both confer up-regulation of the DinB error-prone DNA polymerase, which then makes errors that become mutations in acts of DSB repair via homologous recombination (HR) (7). Whereas up-regulation of DinB is the sole role of SOS in DSB-dependent SIM (8), RpoS additionally licenses the use of DinB (7,9,10) and other low-fidelity DNA polymerases (10) in DSB repair by a mechanism not yet elucidated. This process causes a switch from highfidelity to mutagenic DSB repair under RpoS-inducing stress (7).…”
mentioning
confidence: 99%
“…An approach to circumventing the problem of selection and varying stress level is to use identical growth conditions, but with bacteria in which the level of SIM is under genetic control. A way of doing this is to control a major input into SIM regulation; RpoS has been implicated as a controller of SIM in several laboratories (Galhardo et al 2007;Storvik and Foster 2010;Gutierrez et al 2013). RpoS (also known as s S ) is an alternative RNA polymerase sigma factor and the master stress regulator in E. coli, which is highly variable and dependent on both environmental signals and growth phase (Battesti et al 2011;Hengge 2011).…”
mentioning
confidence: 99%